The Role of Interpersonal Communication of Mulok Teachers in Instilling Malay Cultural Values - Hadi Saputra, Hamanda (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2024)
THE ROLE OF INTERPERSONAL COMMUNICATION OF TEACHERS OF MALANG CULTURE IN INCORPORATING MALAY CULTURE VALUES, Malay Local Content is a subject or study material that contains content and learning processes about the potential and uniqueness of the Malays. Malay Local Content aims for students to understand the superiority and wisdom of the Malays. Riau Malay Culture is a mandatory local content for students from PAUD to SMP/MTs in Riau Province. this study intends to find out how interpersonal communication of teachers is when instilling Malay cultural values ​​to students. By involving 3 informants and informants, namely teachers, this study uses a qualitative research method with data collection techniques using observation, in-depth interviews, and document studies as well as descriptive data analysis techniques. then what can be concluded in this study is as follows: (1). Overall, the role of interpersonal communication of teachers in improving children's knowledge is concluded to be quite good. (2). The language used by teachers is very appropriate in communicating with their students. (3). Non-verbal communication carried out by teachers in interacting with their students is by using movements, additional objects, gestures, facial expressions, symbols and varying voice intonations. The findings of this research paper highlight the importance of teacher interpersonal communication in students’ cultural identity development